MONITORING AND CAPACITY BUILDING OF UNODC IN ADDRESSING HUMAN TRAFFICKING THROUGH GLO.ACT PROGRAM IN AFGHANISTAN 2018-2024 - Aprillia Nursafitri; Renitha Dwi Hapsari (Halu Oleo University, 2025)
This research examines the monitoring and capacity-building efforts conducted by the UNODC under the GLO.ACT program to address human trafficking in Afghanistan from 2018 to 2024. Human trafficking in Afghanistan is a matter of international concern due to the high level of vulnerability caused by conflict, poverty, and weak legal protection systems. This research is based on an analysis of the implementation of the GLO.ACT program in Afghanistan, using a conceptual framework on human trafficking and the theory of International Organisation Implementation with a qualitative approach through a literature review. The findings indicate that the UNODC implemented the GLO.ACT program in Afghanistan through a management approach, which included periodic monitoring and evaluations of the program’s progress. Additionally, capacity-building initiatives were undertaken to enhance the effectiveness of anti-trafficking measures. However, significant challenges, such as political instability and resource constraints, hinder the program’s overall effectiveness. This research highlights the importance of collaboration between international organisations and relevant countries to ensure the program’s sustainability and strengthen efforts to combat human trafficking.